RETRACTED: UNSUR KEMASLAHATAN PADA HIBAH SUAMI – ISTRI - Muhammad Zainuddin Sunarto (Hukum Keluarga Islam IAIN LANGSA, 2020)
RETRACTEDFollowing a rigorous, carefully concerns and considered in the review of the articlepublished in Al-Qadha: Jurnal Hukum Islam dan Perundang-Undangan entitled